Weak dependence between the Brazilian consumer inflation and expected inflation: Non-linear and Copulas methods and a note on the Central Bank's credibility - Moreira R.R. (2014)
By implementing the Copulas method, this work analyses the dependence relationship or structure between the Brazilian consumer observed inflation and the expected inflation, from January 2005 to June 2011. Its results are consistent with some works for the Brazilian case, as the dependence structure measures showed that there exists a weak relationship between those variables, thereby confirming the hypothesis of high credibility for the Brazilian monetary policy under the inflation targeting period. ? 2013 Inderscience Enterprises Ltd.